Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Produk Elektronik Di Tokopedia (Studi Kasus Pengguna Tokopedia Di Cimahi Utara) - Ayi Muhiban; Firman Nugraha Prasetia (POLITEKNIK LP3I, 2026)
This study aims to determine how Product Quality and Price influence the decision to purchase electronic products on Tokopedia (Case Study of Tokopedia Users in North Cimahi). This study uses a quantitative research method through a descriptive and associative approach by distributing questionnaires using Google Forms as a data collection method to 97 respondents. The research unit is Tokopedia users in North Cimahi. The sampling technique is Random Sampling Snowball Sampling technique. Sampling uses the Cochran formula. Based on the results of this study, it shows that Product Quality has an influence on the Decision to Purchase electronic products on Tokopedia users in North Cimahi by 17.9%. In addition, Price also has an influence on the Decision to Purchase electronic products on Tokopedia users in North Cimahi by 20.6%. And simultaneously Product Quality and Price have an influence on the Decision to Purchase electronic products on Tokopedia users in North Cimahi by 38.5%.